ESTUARINE MANAGEMENT AREAS: A PRIORITY RANKING SYSTEM - Olsen, H. F. (Marine Research in Indonesia, 1977)
The Queensland Fisheries Service is the instrumentality responsible for administration of fisheries matters within Queensland, Australia. The Fisheries Act provides legislation to protect, conserve, manage and develop the aquatic resources of the State. As a means of evaluating resource data a priority ranking system is proposed which provides for both quantitative and qualitative assessments of estuaries in terms of regional planning for best land use.